Analisis Penerapan Good Corporate Governance Dan Budaya Lokal Dalam Tata Kelola Keuangan LPD - Kusuma Sari, Putu Eka Sri; Fery Karyada, I Putu (Hita Akuntansi dan Keuangan, 2023)
This study aims to determine (1) the factors causing fraud in the LPD, (2) the implementation of good corporate governance in financial governance in the LPD, and (3) the application of local culture used in financial governance at the LPD Dawan Widang Kelod. This research use desciptive qualitative approach. This study utilizes primary and secondary data collected through interviews, observations, documentation, and literature reviews. The findings of this study reveal that the elements that contribute to LPD fraud are weak organizational structures, weak supervisory functions, absence of a system or refusal to use the system, weak LPD governance, the presence of a ewuh pakewuh culture, and low-quality human resources. Good financial governance practices have not been implemented in LPD Dawan Widang Kelod such as transparency, accountability, responsibility, independence, equality and fairness which are not in accordance with the provisions. LPD Dawan Widang Kelod has implemented the local culture of Tri Kaya Parisudha which can shape the character and integrity of human resources. However, in its implementation it has not been implemented optimally to achieve good financial governance